Alternatively spliced NKp30 isoforms affect the prognosis of gastrointestinal stromal tumors - Delahaye, Nicolas F; Rusakiewicz, Sylvie; Martins, Isabelle; Ménard, Cédric; Roux, Stephan; Lyonnet, Luc; Paul, Pascale; Sarabi, Matthieu; Chaput, Nathalie; Semeraro, Michaela; Minard-Colin, Véronique; Poirier-Colame, Vichnou; et al. (Nature Medicine, 2011)
Gastrointestinal stromal tumors can respond to imatinib mesylate therapy owing to its inhibitory action on tumor cells as well as off-target effects on NK cells. This report shows that a different frequency of genetically determined expression profiles of isoforms of the NK cell receptor NKp30, which show various functional properties, is associated with GIST and influences survival after imatinib treatment. The natural killer (NK) cell receptor NKp30 is involved in the recognition of tumor and dendritic cells (DCs). Here we describe the influence of three NKp30 splice variants on the prognosis of gastrointestinal sarcoma (GIST), a malignancy that expresses NKp30 ligands and that is treated with NK-stimulatory KIT tyrosine kinase inhibitors. Healthy individuals and those with GIST show distinct patterns of transcription of functionally different NKp30 isoforms. In a retrospective analysis of 80 individuals with GIST, predominant expression of the immunosuppressive NKp30c isoform (over the immunostimulatory NKp30a and NKp30b isoforms) was associated with reduced survival of subjects, decreased NKp30-dependent tumor necrosis factor-α (TNF-α) and CD107a release, and defective interferon-γ (IFN-γ) and interleukin-12 (IL-12) secretion in the NK-DC cross-talk that could be restored by blocking of IL-10. Preferential NKp30c expression resulted partly from a single-nucleotide polymorphism at position 3790 in the 3′ untranslated region of the gene encoding NKp30. The genetically determined NKp30 status predicts the clinical outcomes of individuals with GIST independently from KIT mutation.